Language proficiency of FSPPP students in UiTM Melaka City Campus / Puteri Noor Syakila Megat Amaluddin and Amirah Anatie Mohamad Jamaruddin - Megat Amaluddin, Puteri Noor Syakila; Mohamad Jamaruddin, Amirah Anatie (Faculty of Administrative Science and Policy Studies, 2013)
The usage of English language among students is very important. In most universities level, English language is the medium of instruction. English language is a global language and thus it is important to be proficient in order to compete with others in this challenging world. Despite its importance, there are people who are not proficient in English language. Malaysian students, for example, eventhough they have learnt English for 13 years, 6 years during primary education and 5 years in secondary education, they are still not proficient in that subject. Tan Sri Muhyiddin Yassin who is currently Minister of Education wants this problem to be solved urgently because English is the main language in the world in terms of communication and economy (Ministry of Education, 2012).